Serine proteases analysis based on phylogenetic trees constructed from the sequence and structure alignments. - RIBEIRO, C. (2006)
Short Abstract: We compared two approaches to construct phylogenetic trees from a set of serine proteases with deciphered 3D_structure. The first approach: sequence alignment generates a phylogenetic tree; the seccond approach is based on a sequence alignment strictly following the structure alignment. The differences b/w the two is discussed.